Lymphocyte Profile and Immune Checkpoint Expression in Drug-Induced Liver Injury: An Immunophenotyping Study - Cueto-Sánchez, Alejandro; Niu, Hao; Del Campo-Herrera, Enrique; Robles-Díaz, María Mercedes; Sanabria-Cabrera, Judith Adriana; Ortega-Alonso, Aida; García-Cortés, Miren; González-Grande, Rocío; Jiménez-Pérez, Miguel; Ruiz-Cabello, Francisco; Andrade-Bellido, Raúl Jesús; Lucena-González, María Isabel (Wiley, 2021)
The identification of specific HLA risk alleles in drug-induced liver injury (DILI) points toward an important role of the adaptive immune system in DILI development. In this study, we aimed to corroborate the role of an adaptive immune response in DILI through immunophenotyping of leukocyte populations and immune checkpoint expressions. Blood samples were collected from adjudicated DILI (n = 12), acute viral hepatitis (VH; n = 13), acute autoimmune hepatitis (AIH; n = 9), and acute liver injury of unknown etiology (n = 15) at day 1 (recognition), day 7, and day >30. Blood samples from patients with nonalcoholic fatty liver disease (NAFLD; n = 20) and healthy liver controls (HLCs; n = 54) were extracted at one time point. Leukocyte populations and immune checkpoint expressions were determined based on cell surface receptors, except for CTLA-4 that was determined intracellularly, using flow cytometry. At recognition, DILI demonstrated significantly higher levels of activated helper T-cell (P < 0.0001), activated cytotoxic T-cells (P = 0.0003), Th1 (P = 0.0358), intracellular CTLA-4 level in helper T-cells (P = 0.0192), and PD-L1 presenting monocytes (P = 0.0452) than HLC. These levels approached those of HLC over time. No significant differences were found between DILI and VH. However, DILI presented higher level of activated helper T-cells and CTLA-4 than NAFLD and lower PD-L1 level than AIH. Our findings suggest that an adaptive immune response is involved in DILI in which activated CD4+ and CD8+ play an important role. Increased expression of negative immune checkpoints is likely the effect of peripheral tolerance regulation.
Keywords: Hígado -- Enfermedades; Inmunoterapia; Lesión hepática inducida por fármacos; DILI; Sistema inmune; Inmunofenotipificación